2000
DOI: 10.1080/10584600050178942
|View full text |Cite
|
Sign up to set email alerts
|

Gen.com: Youth, Civic Engagement, and the New Information Environment

Abstract: What follows is an exploratory examination of the current disengagement of young Americans from public life, some thoughts on the roots of this disengagement, and speculations on the ways in which new technologies such as the Internet might be used to improve this state of affairs. It is meant to be a starting point for discussion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
306
1
30

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 538 publications
(344 citation statements)
references
References 4 publications
(1 reference statement)
7
306
1
30
Order By: Relevance
“…Along with community service, identification with and participation in a larger social community predict civic integration (Delli Carpini, 2000;Youniss, McLellan, & Yates, 1997). As a template for adult society, the high school community provides the boundaries within which adolescents can begin to develop a sense of community and belonging to a group outside the home.…”
Section: Community Service and Social Integration: Predictors Of Younmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with community service, identification with and participation in a larger social community predict civic integration (Delli Carpini, 2000;Youniss, McLellan, & Yates, 1997). As a template for adult society, the high school community provides the boundaries within which adolescents can begin to develop a sense of community and belonging to a group outside the home.…”
Section: Community Service and Social Integration: Predictors Of Younmentioning
confidence: 99%
“…In another recent investigation of the effects of high school activities on young adult civic outcomes, McFarland and Thomas (2006) found that community service participation during adolescence strongly predicts civic participation during young adulthood. Using both NELS and Add Health survey data in multilevel models predicting an index of adult political participation, the authors explore the effects of involvement in voluntary organizations during high school while controlling Along with community service, identification with and participation in a larger social community predict civic integration (Delli Carpini, 2000;Youniss, McLellan, & Yates, 1997). As a template for adult society, the high school community provides the boundaries within which adolescents can begin to develop a sense of community and belonging to a group outside the home.…”
Section: Community Service and Social Integration: Predictors Of Younmentioning
confidence: 99%
“…Junto de sinais de que o acesso à internet em grande medida reproduz o poder de expressão dos que têm mais conhecimento e informação, apareceram as possibilidades de participação ampliada de segmentos diferenciados -sobretudo os mais jovens. Estudos internacionais consistentemente demonstram que os mais jovens engajam-se na política em ní-vel muito menor do que os mais velhos; eles têm menor probabilidade de mostrar interesse no assunto, votar, participar de atividades não-eleitorais e engajar-se em esforços de mobilização (VERBA, SCHLOZMAN & BRADY, 1995;DELLI CARPINI, 2000;PUTNAM, 2000). A maior presença jovem na internet, um meio que diminui os custos de informar-se e de participar, é um dado promissor -embora estudos recentes recomendem cautela, por constatarem que a baixa motivação dos jovens para a política reproduz-se nos meios digitais (LIVINGSTONE, COLDRY & MARKHAM, 2007).…”
Section: Conclusõesunclassified
“…En otras palabras, esta tesis defiende que Internet puede modificar la lógica de la participación a través de la movilización de individuos y grupos nuevos de individuos que hasta ahora se habían mantenido al margen del proceso participativo (Delli Carpini, 2000;Ward, Gibson y Lusoli, 2003) 3 .…”
Section: Introductionunclassified